Pengeringan Beku Vakum Bengkuang Dengan Memanfaatkan Panas Buang Kondensor Untuk Proses Sublimasi - Brama, Jaka; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Vacuum Freeze Drying is one of the best ways of drying products as freeze drying vacuum drying or preserving materials without a change in physical and chemical properties of materials. This study was a continuation of previous studies that vacuum freeze drying jicama. The results of previous studies which can eliminate 62% moisture content for 24 hours. This current research is to optimize the vacuum freeze drying previous to adding the heater exhaust condenser to the sublimation process.Condenser waste heat with temperatures reaching 40 ° C flowed dryer chamber and propagated on the jicama to speed up the process of sublimation.Keyword: freeze drying vacuum, waste heat recovery condenser, jicama